(3efXheI aj Gdabg GdTGaYis
(3ChdgG (B:s
(3Chdg eHJhQ , hChd GdehLhO efg bhdg (B: (3aEf CJi GdYHO HfaSg adG jCNP eG Ydi GdQOhO LYdG (B[ (3Ke JHY HYO Pdc Hbdjd (B" (3cJGH CMcGe GdaQGFV (B"] s
(3BNQgG (B:s
(3afSCd Gddg GdbHhd hGdQVi HeG bVi hGdYah Yf PfH eVi s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdYfhGfGJ GdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3Gdabg GdTGaYjs